Perlindungan Hukum Hak Cipta Lagu/Musik atas Royalti dalam Perspektif Teori Keadilan Menurut Undang-Undang No. 28 Tahun 2014 Tentang Hak Cipt - Ramadani, Muhammad Aru; H, Hartana; Setiawan, Puguh Aji Hari (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In addition to bullying, pressures in work, family, education, dating problems and economic problems, can support the occurrence of mental disorders, in addition to that there are other factors that can affect one’s mentality such as hereditary or genetic. In an era that is technologically advanced and based on reeconomy and employment sectors where many human job positions are being replaced by technology or robots, as well as the ease of society in accessing various platforms thus triggering and creating a real social disparity value, this convenience of less or less supportive families is as much a pro in the environment. tracing the development of the times, Many pressures come from close people such as family, social and life environment that makes some people lose their health and affect their mental health, this journal discusses the legal implications if it happens to people in mental disorders (ODGJ), deciding to step into the next stage as well as handling it medically if it is felt to need help, as well as when is the right time to go to a professional personnel such as a psychiatrist in order to get the right handling in order to recover and prevent anything else bad from happening.